The conservation, ecology, and distribution of the critically endangered Encephalartos latifrons Lehm - Swart, Carin (Rhodes University, Faculty of Science, Botany Department, 2019)
Cycads have attracted global attention both as horticulturally interesting and often valuable plants; but also as some of the most threatened organisms on the planet. In this thesis I investigate the conservation management, biology, reproductive ecology and distribution of Encephalartos latifrons populations in the wild and draw out conclusions on how best to conserve global cycad biodiversity. I also employ computer-modelling techniques in some of the chapters of this thesis to demonstrate how to improve conservation outcomes for E. latifrons and endangered species in general, where information on the distribution, biology and habitat requirements of such species are inherently limited, often precluding robust conservation decision-making. In Chapter 1 of this thesis I introduce the concept of extinction debt and elucidate the importance of in situ cycad conservation. I explain how the concept of extinction debt relates to single species, as well as give details on the mechanisms causing extinction debt in cycad populations. I introduce the six extinction trajectory threshold model and how this relates to extinction debt in cycads. I discuss the vulnerability of cycads to extinction and give an overview of biodiversity policy in South Africa. I expand on how national and global policies contribute to cycad conservation and present various global initiatives that support threatened species conservation. I conclude Chapter 1 by explaining how computer-based models can assist conservation decision-making for rare, threatened, and endangered species in the face of uncertainty. Chapter 2 of this thesis illustrates how a modelling approach, using limited available historical and present day locality information, is a feasible method to determine areas of suitable habitat for E. latifrons and other critically endangered cycad species where locality information is inherently uncommon. Results from this chapter show that conservation planning through structured decision-making may be improved by the use of computer models, even when locality data are limited. These results may be incorporated into biodiversity conservation plans or used to assist conservation-decision makers when undertaking recovery efforts for E. latifrons and may provide guidance to conservation planners and policy makers when undertaking conservation plans to improve cycad biodiversity both nationally and globally. There was limited information available in the biology and ecological requirements of E. latifrons. This information is important when making policy decisions such as the publication of non-detriment findings and compiling biodiversity management plans for this and other cycad species. Chapter 3 investigates the life-history, population structure, fire response and survival of an in situ E. latifrons population. A demographic census was undertaken between 2013 and 2017 on a previously undiscovered population. Population characteristics of the "new" population were compared to the demographics of a well-known and intensively managed population. Results of this chapter show that at least one in situ E. latifrons population is stable and increasing under current environmental conditions. Importantly, the population is naturally recruiting seedlings without the need for artificial pollination. Demographic information described in this chapter is a necessary precursor to undertaking a Population Viability Assessment for the species. This will assist conservation decision-makers when determining the best conservation management strategy for E. latifrons. It may also be useful to apply generalisatons to other cycad species (with similar life-histories and habitat requirements) where there is limited information available on the species biological and ecological requirements, restricting robust policy conservation decision-making. It was important for this study to determine the extent and variety of cone fauna within existing E. latifrons wild populations. Previous anecdotal evidence suggested that E. latifrons is functionally extinct as a species, but evidence to the contrary was found when a healthy, self-sustaining wild population was discovered to be naturally recruiting. It was important to establish the existence and diversity of male cone faunal species (an important breeding site for weevil pollinators) within wild populations. Chapter 4 set out to determine if potential pollinators exist in the wild and if so, how diverse are they and in what numbers. This is the first comprehensive analysis of cone fauna present in wild E. latifrons populations. Equally important was the need to determine if wild populations are capable of producing viable seeds under conditions conducive to natural pollination. Results of this chapter show that there is a relatively high diversity of insect fauna in the male cones of some wild E. latifrons populations. Furthermore, some wild populations are capable of producing viable seeds through natural pollination; even though they may not be naturally recruiting seedlings into the population. A staggered germination pattern displayed by one of the wild E. latifrons populations was studied, suggesting the evolution of an adaptive trait given the stochastic environment (climatically and disturbances such as fire) within which E. latifrons populations may be found. Species recovery (restoration and/or population augmentation) may be the only conservation solution remaining to save endangered species such as E. latifrons from extinction in the wild. Chapter 5 involves the return of 25 seedlings germinated as part of a seed viability experiment (see Chapter 4) back into a wild population from where they originated. The primary threat to seedling survival at the site was livestock activity (grazing/trampling). The population was subsequently fenced off to mitigate this threat and seedlings planted both inside and outside a fenced area to establish if there was a difference in seedling survival between the unprotected and protected sites. A high percentage (92%) of seedlings planted perished in total. None of the seedlings planted outside the fenced area survived over the monitoring period, while only two seedlings planted within the fenced area survived. Survival of the seedlings inside the fenced area was only after placing individual cages on the seedlings to prevent further losses. The primary causes of death for all seedlings included uprooting, and defoliation with some of the seedlings missing completely. This chapter found that the lack of natural seedling recruitment at the site was as a result of livestock activity. Grazing by livestock poses a significant threat to natural recruitment in some E. latifrons populations. Alternative restoration methods are suggested and protection of seedlings while undertaking a restoration/augmentation programme is emphasised. Developing conservation management plans for rare and/or endangered species is often met with high levels of uncertainty, particularly if there is limited information available on the biology and ecological requirements for the species concerned. Population viability analysis (PVA) is often suggested as a tool to determine conservation management scenarios that may enhance wild population persistence. The standard PVA approach is however problematic as it is a time-consuming process requiring the collection of demographic data over long time periods. In addition, the PVA approach does not take in to account non-biological factors which may impede the effective implementation of conservation plans. Chapter 6 of this thesis makes use of a Multi-Criteria Decision Making (MCDM) approach called the Analytical Hierarchy Process (AHP) to decide on the best conservation management strategy for an E. latifrons population. Sensitivity analysis was completed to test the robustness of the decision and to identify which criteria influenced the original results. In this study, the development of the decision tree and criteria judgements, were made solely by the researcher. It is emphasised that the decision outcome may be biased if not conducted as part of a multi-stakeholder workshop using the same approach. Nevertheless, it is recommended that a Population Viability Risk Management (PVRM) assessment be undertaken for E. latifrons using an MCDM approach such as AHP as a prestudy, before the revision of the Biodiversity Management Plan (BMP) for E. latifrons. This method is particularly useful when non-biological criteria are to be incorporated into the decision-making process. It is also a viable and holistic alternative to the standard PVA approach when developing conservation management plans for rare and endangered species. In Chapter 7 I review the concept of extinction debt in cycads using E. latifrons as an example. I assimilate historical information to understand mechanisms that may have impacted on E. latifrons populations in the past. This was done to understand the scale of extinction time lags on E. latifrons and to relate this to its present position on the exitinction trajectory. I recommend aligning South African policies and biodiversity assessments with international initiatives and draw out general conclusions for the conservation of global cycad biodiversity. I conclude by recommending further research for E. latifrons.
Keywords: Encephalartos; Cycadaceae; Cycads -- Conservation -- South Africa; Botany, Economic -- South Africa; Rare plants -- South Africa; Endangered plants -- South Africa; Wild plant trade -- Law and legislation -- South Africa